Three-Term Hager–Zhang Projection Method for Monotone Nonlinear Equations - Halilu, Abubakar Sani; Majumder, Arunava; Waziri, Mohammed Yusuf; Ahmed, Kabiru; Murtala, Salisu (Vietnam journal of mathematics, 2025)
In this paper, a conjugate gradient method combined with the projection technique of Solodov and Svaiter (Kluwer Academic Publishers, pp. 355–369, 1998 ) to solve monotone nonlinear equations is presented. The proposed method improved the numerical performance of the Hager–Zhang (HZ) method proposed by Waziri et al. (Appl. Math. Comput. 361 , 645–660, 2019 ), by extending its direction to three-term conjugate gradient direction. The proposed method has been shown to be globally convergent under some mild conditions. Numerical experiments show that the proposed method is effective and produces better results than some existing methods.